Globalisation and OECD consumer price inflation - Pain, Nigel (OECD Publishing, 2008)
Over the past 25 years inflation has moderated considerably in all OECD economies. At the same time, the production of many goods and services has become increasingly internationalised and the level of trade between the OECD and non-OECD economies has risen markedly. This paper investigates the extent to which the observed changes in the inflation process can be attributed to the increasing integration of non-OECD economies into the global economy. The results of the analysis show that i) import prices have become a more important driver of domestic consumer prices since the mid-1990s; ii) the sensitivity of inflation to domestic economic conditions has declined whereas the sensitivity to foreign economic conditions has risen, working through import prices; and iii) the strong GDP growth in the non-OECD economies over the past five years has contributed to the growth of real oil and metals prices. A scenario analysis shows that globalisation has put upward pressure on inflation via higher commodity prices and downward pressure via lower non-commodity import prices with the latter effect having dominated in most OECD economies
Keywords: Economics